Legal pluralism in the practice of informed consent among indigenous communities - RA. Sri Hardini; Agustinus Giri Respati; RM. Achmad Roeswandi; Imam Ropii (Science Midwifery, 2026)
The transformation of individual autonomy standards in modern health law often creates a conflict of norms when implemented within the communal social structures of indigenous peoples. This research aims to analyze the dialectics of legal pluralism in the practice of medical informed consent to find a middle ground between centralistic state regulations and the "living law" within indigenous communities. This study employs an empirical legal research method with a socio-legal approach using a descriptive-qualitative design. The results reveal the phenomenon of "collective autonomy," where the validity of medical consent does not merely rely on individual will but is significantly determined by the legitimacy of customary authority and family deliberation mechanisms. Findings indicate that current informed consent practices tend to be legalistic-formal and fail to translate medical risks into local cultural logic, thereby creating judicial vulnerability for both medical personnel and indigenous patients. It is concluded that a reconstruction of the informed consent model based on "Integrative Legal Pluralism" is required, which accommodates communal consent and the use of cultural mediators as a legitimate part of medico-legal procedures. This model offers a strategic solution to achieve a more inclusive healthcare service, respecting the constitutional rights of indigenous peoples while ensuring equitable legal certainty in Indonesia.